2007
DOI: 10.2174/157488807779316973
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplantation from Alternative Donors for High-Risk Acute Leukemia: The Haploidentical Option

Abstract: Much progress has been made in the clinical, biological and technical aspects of the T-cell-depleted full-haplotype mismatched transplants for acute leukemia. Our experience demonstrates that infusing a megadose of extensively T-cell-depleted hematopoietic peripheral blood stem cells after an immuno-myeloablative conditioning regimen in acute leukemia patients ensures sustained engraftment with minimal graft-vs-host disease (GvHD) without the need of any post-transplant immunosuppressive treatment. Since our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…7,8 Renewed interest in haploidentical HSCT has developed with advances such as the use of 'megadose' CD34 þ cell donations to overcome graft rejection and improved T-cell depletion to minimize the incidence of GVHD. 9,10 Despite these advances, two major problems remained-high relapse rates and significant infectionrelated mortality. Pioneering work of the group from Perugia has shown that a subgroup of patients with myeloid malignancies, in which the donor and recipient pairs are mismatched for certain killer Ig-like receptor (KIR) ligands, have a low risk of graft rejection and relapse rate.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Renewed interest in haploidentical HSCT has developed with advances such as the use of 'megadose' CD34 þ cell donations to overcome graft rejection and improved T-cell depletion to minimize the incidence of GVHD. 9,10 Despite these advances, two major problems remained-high relapse rates and significant infectionrelated mortality. Pioneering work of the group from Perugia has shown that a subgroup of patients with myeloid malignancies, in which the donor and recipient pairs are mismatched for certain killer Ig-like receptor (KIR) ligands, have a low risk of graft rejection and relapse rate.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent development of efficient procedures for T-depletion of grafts by CD34+ positive selection [11,12], CMV retinitis has been rarely reported in such patients. In this setting, some authors have shown that this complication occurs as early as day +10, day +42, day +64, and day +107 post-grafting, whilst the patient is severely lymphopenic and CMV is actively replicating [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Standard prophylaxis with acyclovir (3 9 500 mg m -2 day -1 ) was used as prevention of herpes virus infection (HSV, CMV). GVHD prophylaxis consisted of administration of antithymocyte serum (Genzyme Polyclonals, Marcy L'Etoile, France) at a cumulative dose of 15 mg/kg before the stem cell infusion, and T-depletion of the graft by CD34+ positive selection [11,12]. The total number of CD34+ and CD3+ cells infused was 3.13 9 10 6 and 1.6 9 10 4 kg -1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this is the only available method to cure those disorders [3]. Due to limited sources of human leukocyte antigen (HLA)-identical sibling donors in allo-HSCT, unrelated donor (URD) and HLA-haploidentical related donor (RD) hematopoietic stem cell transplantations (HSCT) are more frequently used for the treatment of hematological disorders [4,5,6]. A broader application of HSCT, improvements in transplantation technologies, and the enhanced success rate of HLA-haploidentical RD-HSCT and URD-HSCT are contributing to continuous improvement in the patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%